Bioavailability of Ca, K, Mg and Na in Arabian Yellow Finned Sea Bream (Acanthopagrus arabicus) with Estimated Daily Intake for Human Consumption: Macro-minerals in Acanthopagrus arabicus (Biological Sciences - PJSIR, 2021)
Yellow finned sea bream (Acanthopagrus arabicus) is a commercially important fish of coastal water of Pakistan. It is widely consumed by the people within and outside the country. Therefore, the paper investigates the concentration of macro-minerals (Ca, K, Mg and Na) in its meat and gills. The concentrations of different elements demonstrated statistically significant difference (P < 0.01) between meat and gills of the fish. Significantly higher concentrations of calcium and lower concentrations of potassium and sodium were recorded in gills compared to those in meat. In meat, mean concentrations were found in the order Na (5.41%) > K (3.44%) > Ca (2.16%) > Mg (0.24%), while in gills, the mean concentrations were Ca (57.72%) > Na (3.43%) > K (1.19%) > Mg (0.31%). Statistically significant correlations (P < 0.05) were noted between the body weight and the concentrations of calcium and magnesium in the meat of fish. The results are also compared with estimated daily intake and dietary reference intake values. The present study suggests that Acanthopagrus arabicus is an important source of macro-minerals for human consumption.